STUDY OF THE EFFICACY OF TREATMENT OF MANIFEST IRON DEFICIENCY IN PREGNANT WOMEN WITH TARDIFERON - F.K.Askarova (Scholar Express Journals, 2022)
Anemia is a decrease in the number of erythrocytes and hemoglobin in the blood. Abnormal forms of erythrocytes appear in the blood, as well as changes in the balance of vitamins, reduced number of trace elements and enzymes in the body. During pregnancy, a woman's blood volume increases by 50%, which require more hemoglobin and iron reserves. This is of great importance in the development of the placenta and the baby. Anemia is the most common condition in pregnancy.
Keywords: Anemia; Tardiferone